2017
DOI: 10.1097/rct.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Shortened Mean Transit Time in CT Perfusion With Singular Value Decomposition Analysis in Acute Cerebral Infarction

Abstract: A region of shortened MTT indicated obstructed blood flow, which was attributed to the singular value decomposition method error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, because tMIP was not CTP, which needs a complicated analysis algorithm, it was unaffected by differences among commercial software for analysis, [ 23 ] and analysis error of the basic principles of SVD method. [ 24 ] The tMIP appears to be a much simpler method than CTP for the detection of EIC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because tMIP was not CTP, which needs a complicated analysis algorithm, it was unaffected by differences among commercial software for analysis, [ 23 ] and analysis error of the basic principles of SVD method. [ 24 ] The tMIP appears to be a much simpler method than CTP for the detection of EIC.…”
Section: Discussionmentioning
confidence: 99%
“… 24) Moreover, a paradoxically shortened MTT in patients with AIS with the use of SVD deconvolution algorithms has been reported. 25 , 26) Although the present study showed that the rCBV and rMTT were useful predictors of patient outcome, the rCBV might be considered a suitable parameter in the prediction of patient outcome when taking these matters of measuring the MTT through the SVD deconvolution algorithms into consideration. The CBF is reported as the optimal CTP-derived parameter for predicting the FIV, and the infarct core volume was calculated by the automated perfusion analysis software using the threshold of the relative CBF value.…”
Section: Discussionmentioning
confidence: 60%
“…Step 2: let the sparse matrix obtained after wavelet transform be y and perform random measurement [3]:…”
Section: Optimized Csmri Algorithmmentioning
confidence: 99%